2018
DOI: 10.1016/j.bbi.2017.11.016
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T cells are essential for the effects of enriched environment on hippocampus-dependent behavior, hippocampal neurogenesis and synaptic plasticity

Abstract: Enriched environment (EE) induces plasticity changes in the brain. Recently, CD4 T cells have been shown to be involved in brain plasticity processes. Here, we show that CD8 T cells are required for EE-induced brain plasticity in mice, as revealed by measurements of hippocampal volume, neurogenesis in the DG of the hippocampus, spinogenesis and glutamatergic synaptic function in the CA of the hippocampus. As a consequence, EE-induced behavioral benefits depend, at least in part, on CD8 T cells. In addition, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 56 publications
3
38
1
1
Order By: Relevance
“…Further analysis indicated that the cytokines with different changes between the brain and serum are not completely consistent. Similarly, Zarif et al [55] demonstrated that T lymphocytes purified from the spleen and choroid plexus showed different mRNA transcriptomic profiles as reflected by single-cell RNA seq analyses. The above studies suggest distinguished immune cytokine profiles between the periphery and the brain.…”
Section: Discussionmentioning
confidence: 94%
“…Further analysis indicated that the cytokines with different changes between the brain and serum are not completely consistent. Similarly, Zarif et al [55] demonstrated that T lymphocytes purified from the spleen and choroid plexus showed different mRNA transcriptomic profiles as reflected by single-cell RNA seq analyses. The above studies suggest distinguished immune cytokine profiles between the periphery and the brain.…”
Section: Discussionmentioning
confidence: 94%
“…For the adaptive immune system, both CD4 and CD8 T cells are implicated in influencing networks that underlie learning capacity (Ziv et al, 2006). Zarif et al demonstrated a role for CD8 T cells in learning through the regulation of hippocampal neurogenesis and synaptic plasticity (Zarif et al, 2018). Expression of MHC molecules in the CNS is also required for normal brain development (Bilbo & Schwarz, 2012;Lee et al, 2014).…”
Section: Development Cognition and Behaviormentioning
confidence: 99%
“…Enriched environments are critical to the nervous system of juvenile and adult animals; they are likely to help reverse cognitive and emotional disorders. For mammals, the environment where they grow up noticeably impacted their negative emotional and neuronal development [33][34][35]. As revealed from the results here, for adult rats, simply increasing the diversity of training environments could effectively elevate the learning efficiency of animals without the need to enrich breeding environments.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies have shown that strengthened synaptic connection was found in hippocampus [35]and cortex [33]of animals housed in enriched environments and could be the neural mechanism responsible for the enhanced learning performance. Moreover, activation of prefrontal cortex in rats could enhance active avoidance performance and reduce freezing behavior to neutral conditioned stimuli by inhibiting neuron activities in amygdala [26].…”
Section: Discussionmentioning
confidence: 96%